Strategi Komunikasi Humas PT. Hatonduhan Dearma Sawita Dalam Melaksanakan Program Corporate Social Responsibility - Subroto, Subroto (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2024)
This research is motivated by the public relations communication strategy of PT. Hatonduhan Dearma Sawita in implementing the Corporate Social Responsibility program, the aim of this research is to determine the public relations communication strategy of PT. Hatonduhan Derma Sawita in implementing the Corporate Social Responsibility program. The theories used in this research are communication strategy theory, public relations, corporate social responsibility, and public relations communication strategy. This type of research is descriptive qualitative, namely describing data obtained through research instruments with 3 sources including 1 PT Manager. Hatonduhan Derma Sawita, 1 Public Relations person PT. Hatonduhan Derma Sawita, and 1 PT staff. Hatonduhan Dearma Sawita. The results of this research show that PT. Hatonduhan Derma Sawita has succeeded in making good use of digital media, especially in terms of publishing CSR activities through media such as cyber jet and police news. However, the company has not maximized the potential of social media, because the main focus is still on revenue and profit, as well as strengthening business relationships. Even though they have used outdoor media, there are obstacles related to costs and the difficulty of measuring the effectiveness of CSR campaigns. Therefore, companies need to evaluate their publication strategies and consider making greater use of social media as a tool to achieve broader business and CSR goals.